Gallium and germanium extraction and potential recovery from metallurgical slags. (15th December 2022) - Ettler, Vojtěch; Mihaljevič, Martin; Strnad, Ladislav; Kříbek, Bohdan; Hrstka, Tomáš; Kamona, Fred; Mapani, Ben
Abstract: Metallurgical slags enriched in Ga (144–156 mg/kg) and Ge (285–441 mg/kg) were investigated as potential sources of these technologically critical elements. Conventional mineralogical techniques (SEM/EDS, EPMA) were coupled with automated mineralogy using a Tescan Integrated Mineral Analyzer (TIMA) to quantitatively determine the partitioning of Ga and Ge in the slags. Both elements are primarily bound in the slag glass (90.5–95.4% of Ga and 95.9–96.7% of Ge). Extraction experiments conducted in 0.5 M H2 SO4, 1 M HNO3, and 1 M HCl were used to simulate the hydrometallurgical recovery in view of the potential recovery of Ga and Ge. The leaching of Ga and Ge (and other valuable metals: Zn, Pb) was investigated as a function of time (2–12 h), temperature (25 and 70 °C), and particle size (original granulated slag and ultrafine-milled slag). Compared to other treatments, the highest Ga and Ge extractability was found in 0.5 M H2 SO4 . No significant effect of the particle size, temperature, and time was observed on the Ga and Ge leaching. The optimum conditions for the extraction were: sulfuric acid treatment, original granulated slag (to limit the additional cost of crushing/milling), 25 °C, and at least 6 h of extraction. Despite the high extractabilities of Ga and Ge, more tests are needed to validate the economic feasibility of their full-scale recovery, especially due to the highly fluctuating prices of these elements on the global market. Graphical abstract: Image 1 Highlights: Ga- and Ge-rich metallurgical slags as potential sources of these critical elements. Automated mineralogy: Ga and Ge mostly bound in the slag glass (90.5–96.7%). The highest Ga and Ge extractability in H2 SO4 treatment as compared to other acids. No significant effect of particle size and temperature on the Ga/Ge leaching. More tests needed to validate the economic viability of the Ga and Ge recovery.